Laparoscopic surgery for intestinal obstruction in children due to water absorbing gel beads - Liang, Zhou; Guangjun, Hou; Xianjie, Geng; Xianwei, Zhang; Shah, Jay N. (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Super absorbent polymer gel bead (SAPGB) is increasingly available as toys for children. When ingested it swells by absorbs water and leads to acute intestinal obstruction. Diagnosis and surgery is challenging as its radiolucent, fragile and slippery. We present outcome of our innovative technique of stabilization and removal SAPGBs by laparoscopy minimal invasive surgery (lap-MIS).Methods: This retrospective analyse of outcome of lap-MIS in intestinal obstruction caused by ingestion of foreign body, the SAPGBs, in children who were managed at Children's Hospital Affiliated to Zhengzhou University, China. The outcome variables included removal of SAPGBs, length of hospital stay and postoperative occurrence of anastomotic leak, wound infection, wound dehiscence, re-surgery, or mortality.Results: There were 15 children, male 9 (60%), average age 2 years, and duration of ingestion of SAPGBSs 1.5 days (range 2-4 days), parents gave history of accidental ingestion in 6 (40%). All children had uneventful postoperative recovery after lap-MIS removal of foreign body with no wound infection, anastomotic leak, re-surgery or mortality. Average hospital stay was 4 days (range 3 to 5 days).Conclusions: We had successful outcome lap-MIS with our innovative technique to stabilize and extract foreign bodies, the super water absorbent gel beads, ingested by children.